Agricultural applications for electromagnetic exposure - Aliakbarian, H.; Enayati, A.; Ameri Mahabadi, H.; Soltani, M.A. (IEEE, 2007)
Despite the advances in bug controlling and antifreezing operations of agricultural products, the devastation of Sunne pests and freezing is still enormous. Traditional treatments such as chemical insecticides for bug controlling and covering to avoid freezing have not been sufficient. In the presented paper, new ideas of using electromagnetic treatment for anti-freezing operation, pre-harvest Sunne pest control, and Orchid flower control are introduced.